Hubungan jenis kelamin, status gizi, konsumsi susu dan olahannya dengan kadar asam urat pada lansia - Novianti, Anugrah; Ulfi, Eriliyabuduni; Hartati, Lilik Sri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: The prevalence of gout increased based on age, highest at age 70-79 years 9.3%, age 60-69 years 8%, age 50-59 years 3.7%, and age 40-49 years 3.3%. Meanwhile, based on gender, the prevalence of gout diagnosed with health workers was higher in women at 13.4% compared to men 10.3%. Overweight and obesity can trigger an increase in uric acid levels, so it is one of a risk factor for hyperuricemia. Various high protein and purine foods have long been considered a risk factor for gout. Similarly, the possibility that consumption of dairy products especially cow's milk has a role in protecting the risk of gout based on the results of metabolic studies.Objective: To determined the relationship of sex, body mass index (BMI), dairy products consumption and uric acid levels of the elderly in Cipondoh Sub-District Tangerang.Methods: This study used a cross-sectional design. Research participants were collected by using purposive sampling. Primary data consisted of respondent characteristics, dairy products consumption, BMI, and uric acid levels.Results: The results of this research have shown there was a correlation between BMI and uric acid level p = 0.007, dairy products consumption and uric acid level p = 0.0001, but there was no correlation between sex and uric acid level p = 0.204 in the elderly at Cipondoh Sub-District Tangerang.Conclusion: There was a correlation between BMI, dairy products consumption with uric acid levels of the elderly in Cipondoh Sub-District Tangerang.